Sweet chemistry synthesis of W-O-C based nanometric materials supported on carbon nanotubes - Oseguera-Amezcua, Edwin R.; Cortés-Escobedo, Claudia; González-Huerta, Rosa de G. (Tópicos de Investigación en Ciencias de la Tierra y Materiales, 2014)
The results of the synthesis by soft chemistry of tungsten-based compounds supported on carbon nanotubes (NTC) for their potential use in the oxygen reduction reaction (ORR) in fuel cells of the proton exchange membrane type, PEM for their properties, are shown. acronym in English. For the synthesis by sweet chemistry, also known as the polyol method, complexes of diethylene glycol (DEG) with tungsten and/or platinum salts were used in suspensions of NTC in DEG. Results of the characterization of the crystal structure by X-ray diffraction, morphology by scanning electron microscopy and chemical by infrared spectroscopy are presented. The effect of WOx on NTC/WOx and Pt/NTC/WOx compounds is studied and compared by means of kinetic parameters such as: Tafel slope, exchange current and transfer coefficient, obtained by electrochemical characterization with cyclic voltammetry techniques. (VC) and linear voltammetry (VL) to determine its catalytic activity in the oxygen reduction reaction.